PENGEMBANGAN E-MODUL BERBASIS ANDROID PADA MATA PELAJARAN BAHASA INDONESIA KELAS V MI ASSALAM KOTA BATU - Aprilia, Chofifah Dwi (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2024)
Indonesian is a scientific discipline that directs students to have good and correct skills to practice using Indonesian, both written and spoken. The most important coverage of Indonesian in learning Indonesian at the Madrasah Ibtidaiyah (MI) level is writing and reading. One of the materials that requires reading and writing skills in class V is material about the main idea of a text. In this material, students are assigned to identify the main ideas and important information in non-fiction texts. However, in its implementation, teachers lack innovation in using learning media in the classroom, so students easily get bored and tend to be lazy about reading. Therefore, it is necessary to develop learning media that can increase student motivation. This research uses Research and Development (R&D) research with the Lee & Owens model. Development procedures using the Lee & Owens model include: (1) multimedia needs assessment and analysis; (2) multimedia instructional design; (3) multimedia development; (4) multimedia implementation; and (5) multimedia evaluation. The results of this research and development are in the form of an Android-based e-module learning media product for class V Indonesian language subject theme 5, subthemes 1,2,3 material